PENGARUH WING TIP SUDU ROTOR BLADE TERHADAP UNJUK KERJA WIND TURBIN DENGAN MENGGUNAKAN BLADE NACA 0021 - Firdaus , Muhamad; Firdaus , Rachmat (Journal for Technology and Science, 2024)
The use of energy in Indonesia currently has a growing need for energy, this will have an impact on the condition of the energy crisis, dependence on fossil fuels has a very serious threat, therefore there must be alternative energy as a substitute or as a saver of fuel reserves. Currently available fossils such as wind energy, water energy, and solar energy are very abundant in Indonesia. This study aims to develop wind power plants as a source of alternative energy to produce electrical energy, namely wind turbines. A wind turbine is a tool that functions to convert wind power into mechanical power in the form of a shaft rotation, then this shaft rotation is utilized for power generation. This tool is used to meet energy needs and is also used for alternative energy as an effort to save and reduce dependence on fossil energy. In this problem, the author will develop a tool for the influence of the wing tip of the rotor blade on the performance of the wind turbine. The purpose of this research is to calculate how much influence the wing tip has on the performance of the wind turbine on the electric current produced by the wind turbine. By adding variations to the wing tip using NACA 0021. The data obtained in this study are current (A), voltage (V), turbine power (watts), from the results of the research data it was found that the performance of the wind turbine using NACA0021 was the most optimal using a wing tip. at an angle of 15〗^0 in layer 2 with a voltage value of 12.5 (V), current 2(A), turbine power of 25.35 (watts), and efficiency of 0.844.